Politics of the Russian Language Beyond Russia - Noack, Christian (Edinburgh University Press, 2023)
Russian policy documents increasingly emphasise the importance of miagakaia sila for securing Russia’s foreign policy interests. Looking at the politics of Russian in a range of countries including the Ukraine, Belarus, Kazakhstan, Moldova, Ireland and Germany, this book examines Russian language promotion and its reception in different countries and across different contexts. Bringing together leading scholars in the field, the book examines the politics of the Russian language, the role of the Russian Federation in influencing these politics and the challenges that the promotion of Russian faces in particular contexts across the globe. Taking a comparative approach, the book also examines the institutional set-up and practice of Russia’s language promotion in relation to its British, French and German counterparts and against the history of Soviet cultural diplomacy.